Yield attributes and yield of gobhi sarson (Brassica napus ssp oleifera) and toria (B. rapa) under different levels of nitrogen, phosphorus and farmyard manure in mid-hills of north-western Himalayas - MANKOTIA, B S; SHARMA, H L (The Indian Journal of Agricultural Sciences, 2013)
Significant increase was observed in branches and siliquae/plant of gobhi sarson (Brassica napus L. ssp oleiferaDC. var annua L.) and toria [B. rapa (L.) Thell emend. Metzger; syn B. campestris L. ssp oleifera (Metzger) Sinsk. var toria] on application of N, P and farmyard manure. Higher levels of P and farmyard manure also significantly increasedthe seeds/siliqua in gobhi sarson, hut did not affect its 1 000-seed weight. Yield of both the crops and consequently thetotal yield of the system (gobhi sarson + toria) increased significantly with N, P and farmyard manure application duringboth the years. When farmyard manure was applied, the response to N was significant up to 160 kg N/ha, at which 1 733 kg seed yield/ha was obtained, but in its absence the reponse was significant up to 80 kg N/ha only. Increase in P rate also significantly increased the yield of intercroppirig system, both where farmyard manure was applied as well as not applied. Thus the application of 160 kg N/ha, 35 kg P/ha and fannyard manure @ 5 tonnes/ha increased the productivity.